Photography and Jewish history : five twentieth-century cases - Morris-Reich, Amos 1970- (Jewish culture and contexts, 2022)
"This book develops a method that emphasizes the entwinements of "technology," "ideology," and the medium-specific particularities of photography in five twentieth-century cases in which photography and Jewish history intersect"--